De impact van de Europese Unie op het vastgoed in Brussel: tussen cliché en onderschatting - Nicolas Bernard (Brussels Studies, 2008)
What is the impact of the presence of European institutions on the real estate market in Brussels and its outskirts? Although the question may not be taboo, it is certainly an awkward one. If we blame the European Union for having too great an influence on the housing prices in Brussels, we risk being accused of populism (and insensitivity to the precious contribution made by the EU to the capital city). On the other hand, if we refuse to recognise any correlation, we are accused of being out of touch with reality. As regards the direct impact, this effect is both limited in geographic terms and confined to a certain segment of the built-up area. However, the concentration of EU staff in the affluent neighbourhoods of the capital and in the higher property categories does have indirect effects on the other sectors. As these prosperous areas gradually become financially inaccessible, the demand turns to slightly less exclusive areas – both nearby and further away – which, in turn, experience a rise in prices, and so on. Furthermore, the danger probably also lies in the gentrification caused by the Europeans despite themselves, as they settle in certain run-down neighbourhoods in the city centre. Needless to say, the issue is complex.